Memukul Anak Dan Efeknya Dalam Pembelajaran - Wagiman Manik; Ahmad Akmal Fauzi; Ade Surya; Muhammad Habib Hanzhalah; Al Kautsar Amin; Okta Marlianda (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Physical punishment of children, such as hitting, remains a common practice in education. This study examines the negative impact of physical punishment on learning effectiveness, psychological aspects, and students' academic performance. Research indicates that children who experience physical violence tend to suffer from anxiety, stress, and low motivation to learn, resulting in lower academic achievement. Additionally, physical punishment can lead to emotional disturbances, the development of aggressive behavior, and a decline in social skills. To reduce the practice of physical violence in schools, strategies such as implementing positive discipline, strengthening character education, and increasing awareness among educators and parents about the harmful effects of physical punishment are necessary.